Assessing the role of Information and Communication Technology (ICT) on Business Growth in Sumatera Island, Indonesia - Harsanto, Budi (International Journal of Social Science and Business, 2022)
Information and communication technology (ICT) has become an indispensable part of daily life, including in business. ICT is a technology that is used to analyze, store, and disseminate information, as well as to encourage interconnected and efficient operations in order to support better business performance. This study aims to examine the differences in business growth between companies that used and did not use information and communication technology (ICT). The study takes place on Sumatera Island in Indonesia. Sumatera was chosen because, despite being Indonesia's second most important economic contributor after Java, its ICT development index is low in comparison to other regions. This study made use of the most recent wave of public data from the World Bank's Enterprise Survey for Indonesia. The Enterprise Survey surveyed 194 companies in two provinces: North Sumatera Province and Lampung Province. Chi-square and the Mann-Whitney U Test were used to analyze the data. According to the findings, ICT is more commonly used in large corporations, while it is less commonly used in SMEs. The business growth of companies that use and do not use email differed significantly, whereas the difference in website utilization was insignificant. The minor difference in website usage can be attributed to the growing popularity of intermediaries in innovative e-commerce platforms.